The Contribution of Entertainment, Restauran, and Hotel Taxes to Regional Original Revenue (PAD) in Singkawang City - Qurrotu Aini, Dayang Syahla; Fahmi, Muhammad; Umyana, Ayu (Universitas Muhammadiyah Pontianak, 2025)
This study analyzes the contribution of entertainment, restaurant, and hotel taxes to the Regional Original Revenue (PAD) of Singkawang City from 2019 to 2023. Using a quantitative associative approach and multiple linear regression, 59 secondary data points were analyzed with SPSS 26. The results show that all three taxes have a positive and significant effect on PAD, with restaurant tax being the dominant contributor and entertainment tax the lowest. Collectively, the three taxes explain 100% of the variation in PAD. These findings highlight the importance of optimizing tourism-related taxes through intensification, extensification, and integrated policies to enhance regional fiscal independence..